Climate Resilience and the Adaptation Trap: A Macroeconomic Framework for Joint Fiscal–External Sustainability - António Afonso; José Alves; Jo\~ao Tovar Jalles; Sofia Monteiro (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
Climate change is reshaping sovereign risk and macroeconomic stability by amplifying fiscal and external fragilities. This paper develops a unified framework to assess how climate vulnerability and resilience jointly influence fiscal–external solvency. We construct a market-based sustainability index that integrates time-varying fiscal and external reaction coefficients – estimated using Schlicht's (2021) method-weighted by sovereign yields. Using a global panel of more than 60 economies (1981–2024), we document four key findings. First, structural vulnerability exerts a large and persistent drag on sustainability, even after controlling for macro fundamentals, as higher exposure magnifies expected losses and tightens financing conditions. Second, resilience does not display a strong unconditional effect but significantly mitigates the adverse impact of vulnerability, acting as a state-contingent stabilizer. Third, local projections with smooth transition (LP-STAR) reveal sharp nonlinearities: identical climate shocks trigger modest, short-lived effects in low-vulnerability or high-resilience regimes but cause deep and persistent deterioration when vulnerability is high and resilience weak. Fourth, these dynamics generate an “adaptation trap” – a self-reinforcing cycle where vulnerability raises yields, yields compress fiscal space, and limited adaptation perpetuates vulnerability. Policy implications are clear: resilience investment yields sizable macro-financial returns by reducing expected losses and compressing climate risk premia, while delaying adaptation risks entrenching fragility. Our results highlight the need to embed climate parameters into debt sustainability analyses and sovereign risk frameworks, particularly for emerging markets facing tighter financing constraints.
Keywords: C33; E62; F34; H63; Q54; 330; climate vulnerability; climate resilience; fiscal sustainability; external sustainability; sovereign risk premia